Item Analysis of Multiple Choice Questions of Nahwu Class XII Madrasah Aliyah Pondok Pesantren Islam Al Mukmin Ngruki Sukoharjo: Analisis Butir Soal Pilihan Ganda Mata Pelajaran Nahwu Kelas XII Madrasah Aliyah Pondok Pesantren Islam Al Mukmin Ngruki Sukoharjo - Istianah, Istianah; Arrohmah, Nisa; Nursafitri, Nursafitri; Makruf, Imam (Civilization Research: Journal of Islamic Studies, 2024)
The purpose of this research is to analyze the question items of nahwu class XII of Madrasah Aliyah Pondok Pesantren Islam Al-Mu'min Ngruki. This research uses a quantitative approach and descriptive method. Based on the results of the study, from a total of 30 questions seen from the difficulty of the questions found 3 items categorized as Very Difficult, 2 items categorized as Difficult, 10 items categorized as Moderate, 11 items categorized as Easy, and 4 items categorized as Very Easy. As for the differential power, there is 1 item with a negative index, which means that the item cannot be used, namely number 2, 10 items in the Weak category that cannot be used, 6 items in the Medium category that must be corrected, and 13 items in the Good category, which can be used but requires improvement. Meanwhile, in terms of distractors or question triggers, it can be classified as good if selected ≥ 5% by students. there are 5 items categorized as Not Good because the distractors / triggers do not function properly, namely numbers 9, 24, 25, 27, and 30. And there are 11 items categorized as Less Good, 6 items categorized as Fair, 4 items categorized as Good, and 4 items categorized as Very Good because the distractors / triggers function very well.